2020
DOI: 10.1371/journal.pone.0229329
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of alcohol consumption and its risk factors among university students: A cross-sectional study across six universities in Myanmar

Abstract: Background Globally, alcohol consumption is a significant public health concern and it is one of the most important risk behaviours among university students. Alcohol consumption can lead to poor academic performance, injuries, fights, use of other substances, and risky sexual behaviours among students. However, the study explored the prevalence of alcohol consumption and the associated risk factors among university students since these have not been fully examined in previous research. Therefore, the aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
32
3
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 46 publications
8
32
3
4
Order By: Relevance
“…Although there were a relatively small number (150) of student smokers in our study, we found that smoking correlated positively with the levels of alcohol consumption. Our discovery parallels the reciprocal association between alcohol and tobacco use reported by international colleagues [ 46 ], and in the UK, where there is increased likelihood of students reporting smoking if they also reported high levels of alcohol intake [ 3 ]. The risk-taking culture of university young adults and the long-term health damage due to combined alcohol and smoking provides indication for the need to regulate these activities at universities.…”
Section: Discussionsupporting
confidence: 78%
“…Although there were a relatively small number (150) of student smokers in our study, we found that smoking correlated positively with the levels of alcohol consumption. Our discovery parallels the reciprocal association between alcohol and tobacco use reported by international colleagues [ 46 ], and in the UK, where there is increased likelihood of students reporting smoking if they also reported high levels of alcohol intake [ 3 ]. The risk-taking culture of university young adults and the long-term health damage due to combined alcohol and smoking provides indication for the need to regulate these activities at universities.…”
Section: Discussionsupporting
confidence: 78%
“…Being male was 3 times increased odds of substance use than being women. This nding was in line with several studies conducted elsewhere (5,11,30,31,39,12,19,23,(25)(26)(27)(28)(29). This could be because males are more likely to experiment with things in their life.…”
Section: Substance Use-related Pro Les Among User Respondentssupporting
confidence: 90%
“…It was lower than 43% in Jima University (36) and 46.3% in Debre Markos university (31) in Ethiopia. But it was higher than 16.7% in Adigrat University, Ethiopia (37), 17.5% in Nigeria (38), and 20.3% in Myanmar (29). The variation observed between the current and previous studies could be the difference in the sample size, operational de nition used, and the methodology as a whole.…”
Section: Substance Use-related Pro Les Among User Respondentsmentioning
confidence: 72%
“…Alcohol consumption among school-going adolescents in the United States has been associated with externalizing behaviors such as sensation seeking, conduct problems, and affiliation with delinquent peers while African American ethnicity and internalizing behaviors, such as anxiety, predicted lower alcohol consumption [ 8 ]. In addition findings from a recent study among 15–24-year-old university students in south-east Asia indicate that the prevalence of alcohol consumption is 20.3% and is associated with being male, smoking, peer alcohol consumption, and truancy [ 9 ]. In SSA, surveys among 12–24-year-old students and employed youth in Tanzania (using the Alcohol Use Disorder Identification Test (AUDIT) and timeline-follow-back-calendar (TLFB) methods), and disadvantaged slum dwellers in Uganda (Cut-Annoyed-Guilty-Eye-Opener (CAGE) questionnaire) showed the prevalence of alcohol use disorders to be in the ranges of 12–47% and 11–50%, respectively [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%